Wundersmith : the calling of Morrigan Crow - Townsend, Jessica, 1985- (Townsend, Jessica, 1985- Nevermoor., 2019)
After becoming one of the newest scholars in the elite Wundrous Society, Morrigan Crow must prove that she belongs, all while fighting against a new evil that is determined to bring her and the Society down.